REKONTRUKSI PERSEPSI MASYARAKAT TERHADAP HADITH D{A’IF DALAM RANAH HUKUM ISLAM - rohmanan, mohammad (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2019)
Lately there have been many groups rejecting a tradition or community social activities on the pretext that the activity is based on the hadith d}a'if. They assume that in matters of religion we should use hadith that are truly s}ah}ih. Religion must be cleansed from hadith d}a’if. Departing from this phenomenon the author feels intrigued to restate the attitude of the Islamic scholars in treating hadith dla'if. Through library research, the author tries to trace the literature of the classical scholars in the field of hadith, such as Imam al-Nawawi, al-Bukhari, Ibn Hajar al-Asqalaniy, al-Suyutiy, and others. From this search, the author concluded that almost no ulama rejected the hadith dla'if immediately. They took hadith dla'if in Fadla'il A'mal, history, even in law. Of course with the terms and conditions they have set.